Studying the fusion cutting mechanism in CO2 laser blanking of stainless steel-304 square samples / Abu Mohammed Sifullah - Abu Mohammed, Sifullah (2017)
Stainless steel-304 is an austenitic steel bearing some unique characteristics like high melting point (1450OC), corrosion resistance, weldability, excellent toughness, deep drawing quality etc. These special characteristics widened its application in manufacturing industry. But cutting of stainless steel-304 into desired shape with high accuracy is a great challenge. To confront this challenge of non-conventional cutting process like fusion laser cutting is introduced. It is a thermal process where highly concentrated laser beam is used as heat source to melt or vaporize the material and assist gas is used to blown away the molten material from the workpiece. Consequently desired cutting with narrow-kerf has taken place. But melting and re-solidification associated with laser cutting introduce grain refinement, carbide or sulphide formation and thermal stress near the cutting edge, which cause unwanted heat affected zone (HAZ) and surface cracks. Those unwanted effects of laser cutting need to be identify and must be explain properly by numerical simulation. But comprehensive simulation of fusion laser cutting process of stainless steel-304 sheets is so complex since it is a thermo-mechanical problem. Thus, in this study a coupled thermo-mechanical finite element model was introduced using ANSYS in order to explain the fusion laser cutting mechanism in CO2 laser blanking of square samples. Stainless steel-304 sheet of different thicknesses were cut into 10mm x 10mm square blank under different laser power and speed. The proposed simulation model was able to explain thermal distribution, kerf width, width of heat affected zone (HAZ) and thermal stress. It was assumed that the irradiated laser beam was Gaussian and formulated by using ANSYS parametric design language. Element death methodology was employed for material removal. The thermal stress was calculated from structural analysis where the model was considered as elasto-plastic. The proposed numerical model was validated by experiment. Optical microscope was used to measure the kerf-width and width of HAZ.In addition, scanning electron microscope (SEM) was used to examine the morphological and metallurgical changes along the cut surface. Results of the simulation were validated by experimental and statistical analysis. It justifies that the proposed numerical model shows good agreement with experimental outcomes. In kerfwidth analysis the value of R2 is 0.96 with goodness fitting of 0.9630. Likewise, for width of HAZ the value of R2 is 0.95 with goodness fitting of 0.923. The parametric study indicated that the laser power, cutting speed and material thickness have effect on kerf-width and width of HAZ. However from ANOVA results, it is suggested that laser power is the most significant parameter in laser blanking with 52.44% contribution to kerf width and 72.43% to width of HAZ for material thickness of 1mm. Similarly, 74.67% contribution to kerf width and 64.21% to width of HAZ are observed for material thickness of 3mm. Moreover, higher stress is developed along the cutting edges and maximum at the corner. Thus cracks and surface defects along the cutting edges are observed by SEM, which is more pronounced at the corner. The findings of current study have great implication in laser machining industry. It suggests that higher speed and lower laser power is ideal for square blanks and special concern needs to apply at the corner to reduce surface defects.